Cross-Format Integration of Auditory Number Words and Visual-Arabic Digits: An ERP Study - Finke, Sabrina; Kemény, Ferenc; Clayton, Francina J.; Banfi, Chiara; Steiner, Anna F.; Perchtold-Stefan, Corinna M.; Papousek, Ilona; Göbel, Silke M.; Landerl, Karin (Frontiers in Psychology, 2021)
Converting visual-Arabic digits to auditory number words and vice versa is seemingly effortless for adults. However, it is still unclear whether this process takes place automatically and whether accessing the underlying magnitude representation is necessary during this process. In two event-related potential (ERP) experiments, adults were presented with identical (e.g., “one” and 1) or non-identical (e.g., “one” and 9) number pairs, either unimodally (two visual-Arabic digits) or cross-format (an auditory number word and a visual-Arabic digit). In Experiment 1 (N=17), active task demands required numerical judgments, whereas this was not the case in Experiment 2 (N=19). We found pronounced early ERP markers of numerical identity unimodally in both experiments. In the cross-format conditions, however, we only observed late neural correlates of identity and only if the task required semantic number processing (Experiment 1). These findings suggest that unimodal pairs of digits are automatically integrated, whereas cross-format integration of numerical information occurs more slowly and involves semantic access.